(untitled) (Research, Society and Development, 2021)
The National Policy for the elderly is aimed at serving the elderly population in a special way, given that they need health care in a doubled way, as they are more prone to degenerative diseases. It is noticed that a good portion of the elderly are still affected by metabolic diseases such as Diabetes Mellitus II. The prevalence of elderly people with Diabetes Mellitus II reaches 20%, about one in every five elderly people. The objective of this study is to know the performance of professionals who work in the Family Health Strategy program, in combating, preventing and caring for patients with type II Diabetes Mellitus in the elderly. A descriptive research with a qualitative approach was carried out. Through a field study, which included nurses of both sexes, who work in the Family Health Strategy in the Vila Nova neighborhood in the municipality of Imperatriz-MA. It was raised that nurses perform work aimed at the prevention and treatment of DM. The orientations are carried out most of the time through lectures and conversation circles. The participation of the family in monitoring and supporting the elderly with DM is essential for treatment adherence. And even in the face of the difficulties experienced, both with regard to the lack of materials to work with this group, and the non-adherence of many elderly people to treatment, they manage to carry out actions to promote and prevent DM.